2007
DOI: 10.1111/j.1467-9604.2007.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond words: dance and movement sessions with young people with social, emotional and behavioural difficulties in Estonia

Abstract: T Th hi is s a ar rt ti ic cl le e d de et ta ai il ls s a an n e ex xp pe er ri im me en nt ta al l p pr ro oj je ec ct t i in n E Es st to on ni ia an n s sc ch ho oo ol ls s, , u us si in ng g t th he er ra ap pe eu ut ti ic c d da an nc ce e a an nd d m mo ov ve em me en nt t a as s a a b ba as si is s t to o e ex xp pl lo or re e b be ey yo on nd d t th he e b bo ou un nd da ar ri ie es s o of f l la an ng gu ua ag ge e i in n s su up pp po or rt ti in ng g y yo ou un ng g p pe eo op pl le e t to o d de e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…For students with emotional and behavioral disorders who typically struggle with similar needs, including dance and creative movement activities into the curriculum may be beneficial. Goodgame (2007) provided an excellent example of the positive impact that participation in movement activities has on students' socioemotional competence. Goodgame, a university lecturer and dance and movement specialist, traveled to Estonia to visit three residential schools for students with behavioral, social, and emotional problems.…”
Section: Increasing Socioemotional Awarenessmentioning
confidence: 99%
“…For students with emotional and behavioral disorders who typically struggle with similar needs, including dance and creative movement activities into the curriculum may be beneficial. Goodgame (2007) provided an excellent example of the positive impact that participation in movement activities has on students' socioemotional competence. Goodgame, a university lecturer and dance and movement specialist, traveled to Estonia to visit three residential schools for students with behavioral, social, and emotional problems.…”
Section: Increasing Socioemotional Awarenessmentioning
confidence: 99%
“…The child-reported questionnaires were the: Quality of Life for Children (EQ-5D-Y) (Wille et al, 2010); Child Outcome Rating Scale (CORS) (Low et al, 2012); Child Session Rating Scale (CSRS) (Low et al, 2012). The teacherreported questionnaire was the Strengths and Difficulties Questionnaire with impact supplement (SDQ) (Goodman, 2001). A summary of all measures is presented below, while the study protocol (Moula et al, 2019) provides a more detailed description.…”
Section: Questionnairesmentioning
confidence: 99%
“…Current studies with children and young people showed that DMP can support children with a range of social, emotional, and behavioral difficulties ( Goodgame, 2007 ; Eke and Gent, 2010 ; Ballard et al, 2014 ; Moula et al, 2020a ). In terms of behavioral difficulties, DMP allows children to develop problem-solving abilities and gain methods of self-control, preventing underlying forms of aggression from being escalated into more disruptive behaviors ( Koshland et al, 2004 ; Koolaee et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Karkou & Glasman, 2004). Evidence from qualitative studies demonstrates the benefits of engaging in recreational arts activities for people with disabilities, such as improvements in self-esteem, interpersonal skills, and perceived competence (Ehrich, 2010;Fuller et al, 2009;Goodgame, 2007;Karkou & Glasman, 2004;Kinder & Harland, 2004;Ovenden, 2017;Zitomer, 2016).…”
Section: Introductionmentioning
confidence: 99%